2022
DOI: 10.1302/0301-620x.104b12.bjj-2022-0819.r1
|View full text |Cite
|
Sign up to set email alerts
|

Management of glenoid bone loss in primary reverse shoulder arthroplasty

Abstract: Aims Rates of reverse total shoulder arthroplasty (rTSA) continue to grow. Glenoid bone loss and deformity remains a technical challenge to the surgeon and may reduce improvements in patients’ outcomes. However, there is no consensus as to the optimal surgical technique to best reconstruct these patients’ anatomy. This review aims to compare the outcomes of glenoid bone grafting versus augmented glenoid prostheses in the management of glenoid bone loss in primary reverse total shoulder arthroplasty. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The authors concluded that both bone grafts and augmented glenoid baseplates resulted in excellent range of motion and functional outcomes in primary RSA. They noted that the use of augmented baseplates may lead to fewer complications and revisions ( 52 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The authors concluded that both bone grafts and augmented glenoid baseplates resulted in excellent range of motion and functional outcomes in primary RSA. They noted that the use of augmented baseplates may lead to fewer complications and revisions ( 52 ).…”
Section: Findings and Discussionmentioning
confidence: 99%